INTRAUTERINE GROWTH CHARTS FOR FETAL BIPARIETAL DIAMETER BETWEEN 12 AND 40 WEEKS OF PREGNANCY AND ITS CORRELATION WITH GESTATIONAL AGE - Hebbar, Shripad; Khuraijam, Tracy (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study is to derive intrauterine growth charts for fetal biparietal diameter (BPD) at weekly intervals between 12 and 40 weeks of gestation and to correlate BPD with the gestational age (GA). Methods: In a prospective observational study, a total of 100 women underwent periodic ultrasound examination between 12 and 40 weeks of gestation. Using Microsoft Excel trend line feature, polynomial regression was performed for each of this patient and weekly BPD values were extrapolated. For each week of gestation, we obtained 100 data points, and these were entered into SPSS software to obtain means, standard deviations (SD), and percentile charts for BPD. Relationship between GA and BPD was also established using curvilinear regression. Z scores were used to compare the findings of the present study with Indian, Asian, and non-Asian regions. The incremental growth of BPD per week was also established for the same GA range. Results: The mean Â± SD of BPD value at 12 weeks was 20.4Â±0.94 mm, which gradually increased to 92.5Â±2.89 mm at full term. There was a strong relationship between BPD and GA as indicated by polynomial regression analysis. As gestation advanced, BPD growth rate slowed down from 3.5 mm from mid-pregnancy to around 1 mm at term. Our BPD charts resembled closely Chinese and US growth charts. Conclusion: There was a good mathematical relationship between fetal BPD and GA. The BPD charts and percentile tables derived from the present study help to establish customized growth charts for the local population.